Efficient Synthesis of Anhydrorhodovibrin and Analogues - Yamada, Takeshi; Okada, Keiji; Shinada, Tetsuro; Ohfune, Yasufumi; Hashimoto, Hideki (Synlett, 2012)
The synthesis of anhydrorhodovibrin and two analogues has been achieved in a highly efficient manner using a new Horner–Wadsworth–Emmons reagent bearing the Weinreb amide.
Keywords: polyene; carotenoid; Horner–Wadsworth–Emmons reaction; Weinreb amide